2016
DOI: 10.1186/s40064-016-3716-x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of dairy fat in inducing metabolic syndrome in rats

Abstract: BackgroundThe risk of heart diseases, diabetes and stroke is increased with higher metabolic risk factors. Models of diseases resulting from high-calorie diets have a significant role in pathophysiologic analysis of metabolic syndrome in rodents; but, these diets are considerably different from each other in various studies and may not be very similar to the metabolic syndrome model in humans. This study sought to make a model close to the disease in humans. 20 five-week old male Wistar rats were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…According to our expectations, we found increased glucose plasma levels in the rats from STZ- and HFD-treated groups accompanied by a dramatically decreased (STZ) and significantly increased (HFD) insulin levels. Moreover, the results were similar to the ones established in the literature by us and other authors and confirm the destruction of the pancreatic β -islet cells after STZ injection [ 12 ], whereas HFD feeding led to the subsequent development of insulin resistance development [ 27 , 41 ]. Additionally, we decided upon application of myriocin, a robust, selective inhibitor of ceramide de novo synthesis and, therefore, a potent agent ameliorating insulin resistance [ 12 , 29 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to our expectations, we found increased glucose plasma levels in the rats from STZ- and HFD-treated groups accompanied by a dramatically decreased (STZ) and significantly increased (HFD) insulin levels. Moreover, the results were similar to the ones established in the literature by us and other authors and confirm the destruction of the pancreatic β -islet cells after STZ injection [ 12 ], whereas HFD feeding led to the subsequent development of insulin resistance development [ 27 , 41 ]. Additionally, we decided upon application of myriocin, a robust, selective inhibitor of ceramide de novo synthesis and, therefore, a potent agent ameliorating insulin resistance [ 12 , 29 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the aim of this study was to investigate the diaphragm lipid content and FA composition in relation to altered insulin levels. For this reason, we adopted streptozotocin injection (STZ) and high-fat diet feeding (HFD), two commonly accepted models of type 1 diabetes and preceding type 2 diabetes insulin resistance, respectively [ 27 , 28 ]. In our research, we evaluated diaphragm TAG, DAG, and CER (i.e., well-known markers and/or inducers of skeletal muscle tissue IR) total content, as well as their FA composition [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that fast foods have high levels of calorie and fat, thus leading to high intake of energy, fat, salt, inadequate absorption of vitamins and reluctance to consume fruits and vegetables. The high consumption of such foods is associated with weight gain, obesity and/or the risk of chronic diseases such as diabetes 30 , 31 . Another study on mice showed that fast food diets (with high levels of cholesterol, saturated fat and fructose) were associated with progressive fibrosis 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, obesity is a major risk factor for diseases associated with cartilage (31). The mechanism by which obesity affects the structure and symptoms of cartilage disease is not known accurately, but it can be due to systemic and also local inflammations resulting from the increase in adipose tissue and adipokines levels, especially leptin.…”
Section: Discussionmentioning
confidence: 99%